ANALISIS PENAWARAN EKSPOR TEKSTIL DAN PRODUK TEKSTIL INDONESIA KE ASEAN (Studi Kasus Negara Malaysia, Thailand, Vietnam, Philipina dan Kamboja) - fuadi, faiq (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2018)
International trade plays an important role in economic growth after consumption, investment and government spending. the industrial sector is encouraged to increase international trade, especially non-oil exports. Textiles and textile products (TPT) is one of the most important parts of Indonesian non-oil industry, this is because the textile industry contributes substantially to GDP. This study aimed to analyze the effect of the exchange rate, international prices of textile and textile domestic price index to the volume of Indonesian textile export supply in some ASEAN countries (Malaysia, Thailand, Vietnam, the Philippines and Cambodia).The data used in this research are secondary data in the period January 2011 to December 2014, and the industry codes are used Harmonized System (HS) 50 to 63. The analytical method used is the Fixed Effects Model (FEM) using Least Square Dummy Variable (LSDV).The results showed that the exchange rate, domestic production index are positive and have significant impact on the volume of Indonesian textile exports to ASEAN countries (Malaysia, Thailand, Vietnam, the Philippines and Cambodia). While international prices have positive effect and it not significant.